Additional support for motherhood as a guarantee of preserving family values - S. Ye. Titor (Вестник университета, 2025)
One of the values declared by the President of the Russian Federation is a strong family bond. The Constitution of the Russian Federation and other federal laws actively implement support for family and motherhood. While raising children, a woman is deprived of the opportunity to work full-time and earn her pension rights. As a result, her pension may be lower than that of her husband. Many researchers equate a woman’s domestic childcare labor with full-time labor, which is referred to as parental labor. It proves that a woman should not be disadvantaged in pension rights. At a young age, citizens do not think about it, and understanding comes at elder years when the opportunity for earning a decent pension has already been missed. Measures to strengthen the protection of women, motherhood, and, accordingly, family values by dividing pension rights between spouses, as well as the tax burden, have been analyzed. The German case, where family values are most pronounced and the divorce rate is comparatively low, has been studied. The positive experience has been proposed to be implemented in Russia by introducing appropriate legislative changes.